Multi-scale characterization of the thermal – mechanically isolated bamboo fiber bundles and its potential application on engineered composites. (30th November 2020) - Wang, Xinzhou; Yuan, Zhurun; Zhan, Xianxu; Li, Yongcheng; Li, Maoyi; Shen, Liuhan; Cheng, Dali; Li, Yanjun; Xu, Bin
Highlights: Thermal-mechanical isolation of bamboo fiber bundles (BFB) from moso bamboo culms. Investigation of the chemical and mechanical properties of BFB on cell-wall level. Characterization of the tensile properties of BFB on macro-scale. Analysis the interrelationships among the investigated properties on multi-scale. Discussion the potential application of BFB on the field of engineered composites. Abstract: Bamboo fiber bundles (BFB) were firstly isolated by using the method of high-temperature saturated steam pretreatment following with mechanically rub-twisting. The microstructure, chemical composition, cell-wall mechanics, water absorption and tensile properties of BFB were then characterized and the interrelationships among the investigated properties were analyzed. Results indicated that thermal - mechanical isolation method can effectively extract the fiber bundles from bamboo culms with little damage on the microstructure of bamboo fibers. Both the hygroscopicity and cell-wall mechanics of BFB have been improved due to the degradation of hemicelluloses and increased crystallization degree induced by the saturated steam at the temperature of 180 °C for 30–40 min. BFB presented an obvious advantage in tensile properties as compared to other fibrous materials and were invulnerable to the thermal–mechanical isolation, which opens up the potential applications to reinforce the polymer matrix composites instead of synthetic fibers. Furthermore, the bending strength and modulus of laminated veneer lumber increased significantly with the addition of BFB, indicating that the isolated BFB also has the potential to be applied on engineered composites.